Examining mean-volatility spillovers across national stock markets - Natarajan, Vinodh Kesavaraj (2014)
The study of the stock market in a country and the understanding of the influence of stock market crashes within and across the markets has been the subject matter of many researches academicians and analysts during recent times. In this study we investigate the mean-volatility spillover effects that happen across international stock markets. The study by taking into consideration the stock market returns based on various indices investigates the mean-volatility spillover effects using the GARCH in Mean model for the period January 2002 to (2011). The GARCH-M model seeks to provide useful insights into how information is transmitted and disseminated across stock markets. In particular the model examines the precise and separate measures of return spillovers and volatility spillovers. The analysis provides the evidence of strong mean and volatility spillover across some stock exchanges.